Changes in haematological parameters and serum beta-2-microglobulin levels in CD4+ T-cells-stratified Nigerian HIV patients - Olaniyi, John Ayodele; Emeka, Godwin Joseph; Onifade, Abdulfatah Adekunle; Adeyanju, Alaruru Olusoji; Rahamon, Sheu Kadiri (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Introduction. Reports have shown that there is a rise in beta-2-microglobulin (β2M) concentration in patients with HIV infection and that the degree of elevation correlates well with the extent of disease burden and could be an independent prognostic marker for death. However, there is the dearth of information on the interplay between alteration in haematological profile, a common cause of morbidity and mortality in HIV, and β2M. Aim. Changes in selected haematological parameters and β2M in Nigerian HIV patients stratified based on CD4+ T-cells counts were thus assessed in this study. Material and methods. Forty-eight asymptomatic, drug naive HIV patients were enrolled into this cross-sectional study. Haemoglobin concentration (Hb), packed cell volume (PCV), total and differential white blood cell count, platelet count and CD4+ T-cells count were determined using standard methods while serum levels of β2M were determined using ELISA. Thereafter, the patients were stratified into three groups based on the CD4+ T-cells count. Results. Hb and lymphocyte counts increased with increasing CD4+ T-cells count. In contrast, neutrophils percentage, MCV and MCH reduced with increasing CD4+ T-cells count. The mean lymphocytes percentage was significantly higher while the mean neutrophils percentage was significantly lower in patients with CD4+ T-cells count of 500–800 cells/μl compared with the patients with CD4+ T-cells count <200 cells/μl. Similarly, the mean MCV was significantly lower in patients with CD4+ T-cells count of 500–800 cells/μl compared with patients with CD4+ T-cells count of 200–499 cells/μl and patients with CD4+ T-cells count <200 cells/μl. β2M had significant positive correlation with WBC and neutrophils percentage but had a significant negative correlation with lymphocytes percentage and MCH in patients with CD4+ T-cells count <200 cells/μl. However, β2M had significant positive correlation with PCV, Hb, monocytes and morphology in patients with CD4+ T-cells count of 500–800 cells/μl. Conclusion. It could be concluded from this study that HIV infection is associated with alteration in haematological profile and the alteration is CD4+ T-cells count-dependent. Also, elevation in β2M concentration appears to be a marker of lymphopaenia in patients with low CD4+ T-cells count.
Keywords: beta-2-microglobulin; CD4+ T-cells count; haemocytometry; HIV; lymphopaenia